Ligações de hidrogênio usuais e não usuais: um estudo comparativo das propriedades moleculares e topológicas da densidade eletrônica em HCCH --- HX e HCN --- HX com X = F, CI, CN e CCH - Viana, Marco Antonio de Abreu (2013)
The aim of this work was to study two kinds of intermolecular hydrogen bonding, the non-usual that is represented by the interaction between acetylene and the HX species (C2H2 --- HX) and the usual that is represented by the interaction between hydrogen cyanide and HX species, with X = F, Cl, CN, and HCCH. This interaction promotes changes in the structural, electronic and vibrational properties of the species involved. In this work, we employe d not onlycomputational-quantum methods MP2/6-311 + + G (d, p) and DFT/B3LYP/6-311 + + G (d, p) in order to study the structural, electronic and vibrational properties of those two types of intermolecular hydrogen bonding, but also we employed QTAIM and NBO methods to complement our research. The results have shown no significant differences between the two correlated methods employed for both types of hydrogen bonded complexes, leading us to suggest the use of the DFT/B3LYP method for studies of similar systems to those studied here, due to the lower computational demand. The increase in bond length of the HX species are enhanced due to formation of more linear complexes than T-complexes, in both calculation levels. The intermolecular bond length values in the complex HCN --- HX are smaller than in the complexes HCCH --- HX, and the values from MP2 and DFT/B3LYP are very close in each individual type of hydrogen complex, suggesting that the linear complexes are more stabilized by the formation of hydrogen bonding than the T-complexes, which can be proved by the values of the binding energy of hydrogen in HCN --- HX. Concerning the redshift effect in the harmonic vibrational mode of species HX, due to the formation of intermolecular bond, the values obtained for linear complexes hydrogen are higher than for the corresponding T-complexes, considering both calculation levels. Values were evaluated from the increase in the intensity values of the stretch mode HX bond formation due to intermolecular and, according to the model CCFOM, the term load flow is responsible for the effect on the increase of HX intensity. We also highlight the new vibrational modes, emphasizing the stretch mode of the intermolecular bond. From studies employing QTAIM, it was possible to obtain the values of electron density and the Laplacian electron density and evaluate these parameters in critical points in HX and intermolecular hydrogen bonding, thus confirming the formation of hydrogen bonded complexes. We evaluated the energy difference between π orbitals and lone pair of nitrogen (in HCN), for the species receiving proton and sigma antibonding for the hydrogen of HX, using the method of natural bond orbital variation.